2016
DOI: 10.1093/aob/mcw096
|View full text |Cite
|
Sign up to set email alerts
|

A large historical refugium explains spatial patterns of genetic diversity in a Neotropical savanna tree species

Abstract: Background and Aims The relative role of Pleistocene climate changes in driving the geographic distribution and genetic diversity of South American species is not well known, especially from open biomes such as the Cerrado, the most diverse tropical savanna, encompassing high levels of endemism. Here the effects of Quaternary climatic changes on demographic history, distribution dynamics and genetic diversity of Dimorphandra mollis, an endemic tree species widely distributed in the Cerrado, were investigated.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 77 publications
(89 reference statements)
3
18
0
3
Order By: Relevance
“…Additionally, a single species presented only a slight range retraction, with a large stable area maintained since the LGM (Souza et al, 2016). Higher genetic diversity in the core distribution of diverse plants has also been reported by these phylogeographic studies (Ramos et al, 2007;Novaes et al, 2010Novaes et al, , 2013Ribeiro et al, 2016;Souza et al, 2016).…”
Section: Phylogeography In Seasonal Vegetation Domainssupporting
confidence: 57%
See 2 more Smart Citations
“…Additionally, a single species presented only a slight range retraction, with a large stable area maintained since the LGM (Souza et al, 2016). Higher genetic diversity in the core distribution of diverse plants has also been reported by these phylogeographic studies (Ramos et al, 2007;Novaes et al, 2010Novaes et al, , 2013Ribeiro et al, 2016;Souza et al, 2016).…”
Section: Phylogeography In Seasonal Vegetation Domainssupporting
confidence: 57%
“…Nevertheless, retraction with population subdivision in multiple refugia during the LGM has been recorded for a savanna tree species from central Brazil (Collevatti et al, 2012a) and a palm species restricted to wetlands (Lima et al, 2014). Additionally, a single species presented only a slight range retraction, with a large stable area maintained since the LGM (Souza et al, 2016). Higher genetic diversity in the core distribution of diverse plants has also been reported by these phylogeographic studies (Ramos et al, 2007;Novaes et al, 2010Novaes et al, , 2013Ribeiro et al, 2016;Souza et al, 2016).…”
Section: Phylogeography In Seasonal Vegetation Domainsmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, our study revealed an unexpected cryptic species in B. coccolobifolia from the central and northern areas of the CC, an area reportedly of high species richness (Ratter et al., ). Other phylogeographic studies on Cerrado trees suggest the highest genetic diversity occurs in central areas of the Cerrado as well (e.g., Collevatti, Castro, Lima, & Telles, ; Novaes, Lemos‐Filho, Ribeiro, & Lovato, ; Souza, Collevatti, Lima‐Ribeiro, Lemos‐Filho, & Lovato, ); however, many of these have limited sampling of northern areas. Our results, as those with more extensive sampling (Collevatti, Terribile, Diniz, & Lima‐Ribeiro, ; Ribeiro, Lemos, Buzatti, Lovato, & Heuertz, ) have revealed high genetic diversity in north‐eastern plant populations, highlighting the importance of these areas to conservation efforts of the Cerrado, especially since these areas are part of an expanding agricultural frontier.…”
Section: Discussionmentioning
confidence: 99%
“…A área climaticamente estável para a região central do Cerrado -área core -ao longo do tempo (UMG, presente e futuro) é reconhecida e identificada por modelagem de nicho ecológico para diversas espécies de plantas desse ecossistema (Terribile et al 2012;Bueno et al 2017). Os trabalhos filogeográficos acoplados à modelagem para plantas de Cerrado são concordantes em identificar tal região como climaticamente de maior adequabilidade no UMG e, detentora de maior diversidade genética atual (Collevatti et al 2012a;Collevatti et al 2012b;Collevatti et al 2014;De Lima et al 2014;Collevatti et al 2015;Souza et al 2017).…”
Section: História Biogeográfica Dos Ecossistemas Secosunclassified